Does Location Matter? Fear of Crime and its Determinants in Disadvantaged and More Affluent Neighborhoods in Czechia - Krulichová, Eva (European journal on criminal policy and research, 2024)
Despite a long and rich history of fear of crime research, studies which focus on the importance of local specifics are rather limited. This study fills this gap by analyzing fear of crime—measured as concerns about crime and feeling of safety—among residents of disadvantaged neighborhoods. Drawing on victimization and vulnerability theories, the aim of the study is to examine fear of crime and its determinants and assess whether there are significant differences between people living in disadvantaged and more affluent neighborhoods in Czech municipalities. For this purpose, the data obtained from a cross-sectional face-to-face survey carried out across 13 regions of Czechia were used and a hierarchical binary logistic regression analysis was employed. In line with existing literature on fear of crime in the general population, the results of the analysis confirm that fear of crime among inhabitants of disadvantaged neighborhoods is mainly associated with crime-related variables. The strongest effect was found with respect to crime trend perception, with those who perceived crime in their municipality to be increasing being more fearful than those who perceived it to be stable. Higher levels of fear of crime were observed among inhabitants of disadvantaged neighborhoods, though the effect of locality proved negligible. In addition, once respondents perceived crime to be on the rise, the difference between fear of crime among inhabitants of SELs and non-SELs became blurred.